SURVIVABILITY OF PSEUDOMONAS PUTIDA RS-198 IN LIQUID FORMULATIONS AND EVALUATION ITS GROWTH-PROMOTING ABILITIES ON COTTON - Y. H. He; Y. J. Peng; Z. S. Wu; Y. J. Han; Y. Y. Dang (Journal of Animal and Plant Sciences, 2015)
This study was aimed to screen nutrient carriers, additives, and major chemical fertilizer components for the development liquid formulations of Pseudomonas putid Rs-198 bacterial strain. The number of viable colony forming cells in the formulation amended with corn flour, urea, bentonite, sodium carboxymethyl cellulose, and sodium alginate were found to be 1 × 108 CFU/ml after six months at 25±3°C. D- and Z-values of strain Rs-198 formulated with different substances were significantly higher than that control at 40-60°C. Moreover, the D- and Z-values of strain Rs-198 incorporated in chemical fertilizer nutrient components was slightly differed at the same temperature however was significantly higher as compared to control. Pot study showed that the inoculation of developed four Pseudomonas putida Rs-198 liquid formulations was beneficial in terms of cotton growth under salt stress conditions; as a result, germination rate and biomass were significant increased. These formulations may alleviate salt stress by promoting soluble protein content or decreasing proline and malondialdehyde accumulation in cotton.
Keywords: P. putida Rs-198; survivability; biofertilizer; inoculation; cotton